PENGGALIAN KAIDAH ASOSIASI UNTUK MENDAPATKAN MODEL PERILAKU KONSUMEN - anas, azwar (STKIP PGRI Sumatera Barat, 2017)
The process of buying and selling will occur if their purchases of goods by the consumer to the trader, both traders in traditional markets, modern, mini market or other small stores. In purchasing goods, consumers usually buy different types of items at once. It is based on the efforts to fulfill the daily basic needs. Data owned by an institution is one of the assets of the institution. Their daily trade transactions will further multiply the number of transaction data. The amount of transaction data so large it could be a problem if traders can not use it wisely. In this study, researchers will utilize a priori algorithm to group data based on the purchase of goods tendency to appear together in a purchase of goods. The method I use in this case is a priori algorithm. Meanwhile, to conduct tests on the a priori algorithm analysis, the authors use data mining software Orange. The end result of this research is the description of consumer behavior towards the purchase of goods, so that could be a reference to the placement of goods in accordance with their preferences purchased by consumers. In this study the authors simply using a priori algorithm, the authors further expected to be able to combine a couple of similar algorithms, in order to produce more accurate information.